Klaim Asuransi Muatan Kapal Laut (Marine Cargo Insurance) sebagai Wujud Pertanggungjawaban Freight Forwarder pada PT Pelayaran Meratus Line - kundori; Ali Imran Ritonga; Karolus G. Sengadji; Hilda Emeraldo Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2021)
One of the activities carried out by freight forwarders is to be responsible for the delivery management system and goods arrangement to be efficient, precise, and safe. Freight forwarder activities become an inseparable unit, information and strategies for document management and shipping procedures aim to provide services or management of all required activities. The purpose of this study is to examine the form of responsibility of the shipping company in completing the responsibility for the goods loaded which may be damaged or lost when loaded using a commercial ship and what documents are needed for its management. This study used a qualitative method approach and a descriptive approach to explain the process, the sample was taken at PT. Pelayaran Meratus Line, the representation is expected to be given by this sample. Data collection techniques by means of observation, interviews, literature study, and documentation. Data analysis is done by reducing the data and drawing conclusions. The results of this study can be described as follows: PT. Pelayaran Meratus Line manages documents for goods to be exported and opens an insurance policy for cargo to be transported so that if there is damage or lack of excess goods, an insurance claim can be submitted so as not to cause losses between the two companies. The managerial recommendation for the company is that the documents required for filing an insurance claim must be prepared completely from the beginning with the aim that when a claim occurs between the company and the insurer, they are able to make the disposition of the report optimally.